Structure of even-even actinides in the interacting boson model and the N = 152 subshell closure - Rikovska, J; Bonatsos, D (1988)
We show that a wide range of deformed actinides can be described in terms of an interacting boson model hamiltonian with three parameters, two of them [including the coefficient of the only SU(3) symmetry breaking term] remaining almost constant over the whole region. In addition to ground γ1 and β1 spectra, B(E2:0g+ → 2g+) values are well reproduced with no extra adjustable parameters for nuclei with 136≤N≤146, while for nuclei beyond N = 146 an effective boson number has to be considered in order to fit the observed in the B(E2:0+g → 2+g) values, which is due to the presensce of a subshell closure at N = 152. The sensitive dependence of the B(E2:0g+→2g+) values on the effective boson numbers is emphasized. β1 → ground and β1 → ground transitions are fitted by breaking the SU(3) symmetry of the E2 transition operator. © 1988.